Waste lube oil re-refining plant - Jaleco, Meildrick T., et al. (Miagao, Iloilo, Philippines SOTECH, UPVisayas, 2013)
A plant design was done for the production of pure lube oil.
Sotech thesis-Plant Design
Keywords: Lube oil